Implementation of Australia’s renewed cervical screening program: Preparedness of general practitioners and nurses - Sultana, Farhana; Roeske, Lara; Malloy, Michael J.; McDermott, Tracey L.; Saville, Marion; Brotherton, Julia M. L. (PLOS ONE, 2020)
The National Cervical Screening Program (NCSP) in Australia underwent major changes on December 1st, 2017. The program changed from 2-yearly Pap testing for women aged 18–69 years to 5-yearly HPV testing for women aged 25–74 years including differential management pathways for oncogenic HPV 16/18 positive versus HPV non16/18 positive test results and the option of self-collection for under-screened women. We conducted a survey among cervical screening providers in primary care to assess their level of preparedness in undertaking cervical screening before (pre-renewal) and after (post-renewal) the new program was implemented. Surveys were conducted between 14th August and 30th November 2017 (pre-renewal) and 9th February and 26th October 2018 (post-renewal) among cervical screening providers who attended education sessions related to the new guidelines. Preparedness was assessed in three areas: 1) level of comfort implementing the new guidelines (7 questions), 2) level of confidence in their ability to convey information about the new guidelines (9 questions) and 3) level of agreement regarding access to resources to support implementation (11 questions). Proportions were calculated for each question response and pre- and post-renewal periods compared using generalised linear models. Open-ended questions related to anticipated barriers and ways to overcome barriers were also included in the questionnaires. Compared to the pre-renewal period, a higher proportion of practitioners in the post-renewal period were more comfortable offering routine screening to women ≥25 years (p = 0.005) and more confident explaining the rationale for not screening before 25 years (p = 0.015); confident explaining a positive HPV 16/18 (p = 0.04) and HPV non 16/18(p = 0.013) test result and were comfortable with not referring women with a positive HPV non 16/18 test result and low grade/negative cytology for colposcopy (p = 0.01). A higher proportion of Victorian practitioners in the post-renewal period sample were also comfortable (p = 0.04) and confident (p = 0.015) recommending self-collection to under-screened women and agreed that self-collection is a reliable test (p = 0.003). The most commonly reported suggestion was to provide information, education and communication materials to both patients and practitioners. Compared to the pre-renewal period, practitioners in the post-renewal period were better prepared to implement the renewed screening program. Healthcare providers require further support to implement the self-collection pathway.